Degradation of lignin β‐aryl ether units in Arabidopsis thaliana expressing LigD, LigF and LigG from Sphingomonas paucimobilis SYK‐6 - Mnich, Ewelina (Plant Biotechnol J, 2016)
Lignin is a major polymer in the secondary plant cell wall and composed of hydrophobic interlinked hydroxyphenylpropanoid units. The presence of lignin hampers conversion of plant biomass into biofuels; plants with modified lignin are therefore being investigated for increased digestibility. The bacterium Sphingomonas paucimobilis produces lignin‐degrading enzymes including LigD, LigF and LigG involved in cleaving the most abundant lignin interunit linkage, the β‐aryl ether bond. In this study, we expressed the LigD, LigF and LigG (LigDFG) genes in Arabidopsis thaliana to introduce postlignification modifications into the lignin structure. The three enzymes were targeted to the secretory pathway. Phenolic metabolite profiling and 2D HSQC NMR of the transgenic lines showed an increase in oxidized guaiacyl and syringyl units without concomitant increase in oxidized β‐aryl ether units, showing lignin bond cleavage. Saccharification yield increased significantly in transgenic lines expressing LigDFG, showing the applicability of our approach. Additional new information on substrate specificity of the LigDFG enzymes is also provided.